Linking Hierarchy Culture, Market Culture and Innovation Orientation: Moderating Roles of Causation and Effectuation - Al Maazmi, Khairia Ghuloum; Abubakar, Yazid Abdullahi; Raziq, Muhammad Mustafa (International Review of Management and Marketing, 2024)
This paper aims to examine the influence of hierarchy and market cultures on firm’s innovation orientation. Also, it explores the moderating roles of the two decision-making logics, which are causation and effectuation on the relationship between hierarchy and market organizational cultures and innovation orientation. The current study extends past research on organizational culture and innovation, by being most likely the first study to examine the extent to which the relationship between hierarchical culture and SME innovation orientation is moderated by causal logic; and the extent to which effectual reasoning moderates the relationship between market culture and the innovation orientation of SMEs. The study utilizes survey data from 206 small and medium sized enterprises (SMEs) in the manufacturing and services sectors of the United Arab Emirates (UAE), that is analyzed using SmartPLS. The results of this study suggest that causation moderates the relationship between hierarchical culture and SME innovation orientation. Furthermore, market culture is only positively related to SME’s innovation orientation when effectuation moderates the relationship.